2022
DOI: 10.1039/d1tc05243h
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional color-tuning luminescent Ln@Zr-MOFs for white LEDs and sensitive, ultrafast detection of nitrobenzene in aqueous media

Abstract: Sensitive and rapid detection of nitrobenzene in aqueous media using a fluorescent Eu@Zr-MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…S18 †), it is worth attempting to achieve luminescence emission tuning and white-light emission of compound 1 by encapsulating Eu 3+ ion with characteristic red luminescence and Tb 3+ ion with characteristic green emission. 41,42 Judging from the consistency of the PXRD spectra (Fig. S19 †), the basic frameworks of Ln 3+ @compound 1 are still retained (total concentration: 50 mM).…”
Section: mentioning
confidence: 91%
See 1 more Smart Citation
“…S18 †), it is worth attempting to achieve luminescence emission tuning and white-light emission of compound 1 by encapsulating Eu 3+ ion with characteristic red luminescence and Tb 3+ ion with characteristic green emission. 41,42 Judging from the consistency of the PXRD spectra (Fig. S19 †), the basic frameworks of Ln 3+ @compound 1 are still retained (total concentration: 50 mM).…”
Section: mentioning
confidence: 91%
“…Meanwhile, the N 1s peak shifts to a high binding energy after encapsulating Ln 3+ ions, indicating the interaction of Ln 3+ and nitrogen atoms. 41 Then, the luminescence spectra of Ln 3+ @compound 1 in the solid state were studied in detail. As shown in Fig.…”
Section: mentioning
confidence: 99%
“…34 This kind of MOF generally has a novel topological structure, various adsorption sites, and adjustable luminescence. 35 For example, Liu et al constructed a heterometallic MOF using H 3 TATAB, and the MOF showed a 3D doubly interpenetrated framework and could be used as a fluorescent sensor for nitenpyram. 36 Our group synthesized a Tb-MOF via 2,4,6tris(3,5-dicarboxylphenylamino)-1,3,5-triazine (H 6 TDPAT), 37 which showed a 3D microporous structure; this Tb-MOF could be used as a multifunctional sensor toward colchicine and so forth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among triazine polycarboxylic ligands, symmetric triazine tricarboxylic ligands, triazine tetracarboxylic ligands, and triazine hexacarboxylic ligands have been studied emphatically because their symmetries are high and easy to form porous networks . This kind of MOF generally has a novel topological structure, various adsorption sites, and adjustable luminescence . For example, Liu et al constructed a heterometallic MOF using H 3 TATAB, and the MOF showed a 3D doubly interpenetrated framework and could be used as a fluorescent sensor for nitenpyram .…”
Section: Introductionmentioning
confidence: 99%
“…Systems of this kind could also be used for other analytes detection, such as nitrobenzene (NB), which should be controlled in wastewater to protect the human health and natural environment. Partial replacement of terephthalic acid (H 2 BDC) ligands of UiO-66 MOF with m-phthalic acid (m-H 2 BDC) followed by modification with Ln 3+ (Ln 3+ = Eu 3+ , Tb 3+ ) yielded bifunctional Ln@Zr-MOFs [ 151 ]. It was found that Eu 10 @Zr-MOFs are suitable for turn-off fluorescent switch of NB, since the latter can easily quench the red emission from Eu 3+ through a photoinduced electron transfer (PET) process between NB and its ligands.…”
Section: Tuning the Properties Of Composites Through The Introduction...mentioning
confidence: 99%